2003
DOI: 10.1007/s00436-003-0938-y
|View full text |Cite
|
Sign up to set email alerts
|

Dietary supplementation with Echinacea and development of immunity to challenge infection with coccidia

Abstract: An experiment was conducted to examine the effects of dietary supplementation with 0.1% and 0.5% ground root preparations of Echinacea purpurea (EP; common name: purple cone flower) on the development of immunity following live vaccination and subsequent challenge with multiple coccidia species in an experimental model using a commercial live vaccine preparation. Effects of immunization and EP supplementation on weight gains before challenge, and weight gains, lesion scores and plasma levels of carotenoids and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 21 publications
2
29
0
Order By: Relevance
“…The results of research conducted under an organic rearing system, which forbids the use of coccidiostats, demonstrate that an extract of oregano and vaccine can be an effective part of the prevention of coccidiosis in alternative rearing systems (Waldenstedt, 2003). Feed supplementation with 0.1% or 0.5% of an immunopotentiator, Echinacea purpurea, during the first two weeks of life has been demonstrated to significantly improve BWG and reduce total lesion scores in vaccinated broilers, as compared with those given a live vaccination alone (Allen, 2003). Similarly, sage, thyme, and their phenols, such as cineol, borneol, thymol and carvacrol, have also been investigated for their anticoccidial activity (Szabóová et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The results of research conducted under an organic rearing system, which forbids the use of coccidiostats, demonstrate that an extract of oregano and vaccine can be an effective part of the prevention of coccidiosis in alternative rearing systems (Waldenstedt, 2003). Feed supplementation with 0.1% or 0.5% of an immunopotentiator, Echinacea purpurea, during the first two weeks of life has been demonstrated to significantly improve BWG and reduce total lesion scores in vaccinated broilers, as compared with those given a live vaccination alone (Allen, 2003). Similarly, sage, thyme, and their phenols, such as cineol, borneol, thymol and carvacrol, have also been investigated for their anticoccidial activity (Szabóová et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Oregano extract used to supplement vaccination for the prevention of coccidiosis in organically reared chickens has also been shown to have a positive effect on weight gain in uninfected birds (Waldenstedt, 2003). Feed supplementation with 0.1 or 0.5% immunopotential Echinacea purpurea during the first 2 weeks of life has been demonstrated to significantly improve BWG and reduce total lesion scores in vaccinated broilers, as compared with those given a live vaccination alone (Allen, 2003). Similarly, the anticoccidial effect exerted by sage, thyme and their phenols, such as cineol, borneol, thymol and carvacrol has been established (Ibrir et al, 2001;Szaboova et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that using EP root extract as a dietary supplement significantly decreased lesions in the intestines of poultry contaminated with the protozoan parasite Coccidia. It also enhanced the health of the birds in comparison with controls (26).…”
Section: Discussionmentioning
confidence: 89%
“…Allen found that EP can promote the immune response to live vaccination and may provide protective immunostimulation in the incidence of the natural coccidian inhabitants in the litter (26). Böhmer et al showed same results in the case of ascending antibody titers against SRBCs in broilers using EP for immune system enhancement (10).…”
Section: Discussionmentioning
confidence: 90%